Setting Koordinasi Relai Arus Lebih Pada Tranformator Daya 60 MVA 150 KV dan Penyulang 20 KV: Overcurrent Relay Coordination Setting On Power Transformer 60 MVA 150 KV and Feeder 20 KV - Sari , Humaira; Gunoro , Gunoro (Politeknik Negeri Medan, 2022)
Abstract Fault that may occur in the electric power transmission line can cause damage to equipment and electrical loads if the fault is not isolated immediately. The purpose of this research was to determine the value of the overcurrent relay protection setting on a 60 MVA power transformer and a 20 KV feeder and how the relay coordinates. This research method uses observation and data collection methods to then analyze the settings and coordination between relays. Location of data collection is done at PT. PLN ULTG Paya Pasir, GI Labuhan Medan City, North Sumatera on 09 December 2019 to 22 May 2020. From the results of the research, the setting current on the 150 kV side is 277 A and on the 20 kV side it is 2078 A, while on the feeder side it is 960 A. The overcurrent relay at the Labuhan Substation works at a maximum short circuit current of 12430.75 A with a working time of 0.29 seconds on the feeder side, 0.92 seconds on the 20 kV side, and 1.38 seconds on the 150kV side. it should be checked on the substation equipment, it must always be checked, especially on the installed relays and it is also necessary to check and evaluate the relay settings at other substations. Keywords: relay, coordination, OCR, setting Abstrak Gangguan yang mungkin terjadi di sebuah jaringan transmisi tenaga listrik dapat menimbulkan kerusakan pada peralatan maupun beban-beban listrik apabila gangguan tersebut tidak segera diisolir. Tujuan penelitian ini adalah untuk menentukan besarnya nilai setting proteksi relai arus lebih pada transformator Daya 60 MVA dan penyulang 20 KV dan bagaimana koordinasi antara relay tersebut. Metode penelitian ini menggunakan metode observasi dan pengambilan data untuk kemudian melakukan analisa setting dan koordinasi antara relay. Tempat pengambilan data dilakukan di PT.PLN ULTG Paya Pasir, GI Labuhan Kota Medan, Sumatera Utara pada tanggal 09 Desember 2019 s/d 22 Mei 2020. Dari hasil penelitian diperoleh arus setting pada sisi 150 kV sebesar 277 A dan pada sisi 20 kV sebesar 2078 A, sedangkan pada sisi penyulang 960 A. Relai arus lebih di GI Labuhan bekerja pada gangguan arus hubung singkat maksimum 12430,75 A dengan waktu kerja 0,29 detik pada sisi penyulang, 0,92 detik pada sisi 20 kV, dan 1,38 detik pada sisi 150kV. sebaiknya pengecekan peralatan gardu induk hendaknya selalu di periksa, terutama pada relai-relai yang terpasang dan hendaknya juga perlu dilakukan pengecekan dan evaluasi setting relai pada gardu induk lainnya. Kata Kunci : relay, koordinasi, OCR, penyetelan